Potential applications of the Escherichia coli heat shock response in synthetic biology - Rodrigues, Joana Lúcia Lima Correia (2018)
The Escherichia coli heat shock response (HSR) is a complex mechanism triggered by heat shock and by a variety of other growth-impairing stresses. We explore here the potential use of the E. coli HSR mechanism in synthetic biology approaches. Several components of the regulatory mechanism (such as heat shock promoters, proteins, and RNA thermosensors) can be extremely valuable in the creation of a toolbox of well-characterized biological parts to construct biosensors or microbial cell factories with applications in the environment, industry, or healthcare. In the future, these systems can be used for instance to detect a pollutant in water, to regulate and optimize the production of a compound with industrial relevance, or to administer a therapeutic agent in vivo.